Soil quality and vulnerability in a Mediterranean natural ecosystem of Central Italy. - Francaviglia, R.; Gataleta, L.; Marchionni, M.; Trinchera, A.; Aromolo, R.; Benedetti, A.; Nisini, L.; Morselli, L.; Brusori, B.; Olivieri, P.; Bernardi, E. (Chemosphere, 2004)
Wet and dry atmospheric depositions and soil chemical and microbiological properties were determined in a Mediterranean natural ecosystem of Central Italy near Rome (Castelporziano Estate). The monitoring of depositions permitted us to quantify the exceedances of S and N compounds (expressed as eqH(+)ha(-1)year(-1)) over the critical loads of acidity. Critical loads, i.e. the quantity of a substance which a part of the environment can tolerate without adverse effects occurring, were determined adopting the level 0 methodology following the UN/ECE Convention on Long-range Transboundary Air Pollution. Deposition data were available for the period 1992-1997, and acidity exceedances were referred to the main vegetation types present in the area. Results showed that most part of the Estate has a medium degree of vulnerability to acidification, and the corresponding risk of acidification deriving from the exceedances of atmospheric deposition was rather low. The study of soil chemical and microbiological properties included mainly total soil organic carbon (SOC), microbial biomass-C, biomass-C/SOC, soil respiration, and metabolic quotient (qCO2). Soil organic C metabolism has been discussed on the basis of the results from eight sampling sites.
The following values have no corresponding Zotero field: accession-num: 14987944
Keywords: Acidification; Atmospheric depositions; Biological indicators; Critical loads; Soil microbial biomass; Soil organic carbon

Soil quality and vulnerability in a Mediterranean natural ecosystem of Central Italy. - Francaviglia, R; Gataleta, L; Marchionni, M; Trinchera, A; Aromolo, R; Benedetti, A; Nisini, L; Morselli, L; Brusori, B; Olivieri, P; Bernardi, E (Chemosphere, 2004)
Wet and dry atmospheric depositions and soil chemical and microbiological properties were determined in a Mediterranean natural ecosystem of Central Italy near Rome (Castelporziano Estate). The monitoring of depositions permitted us to quantify the exceedances of S and N compounds (expressed as eqH(+)ha(-1)year(-1)) over the critical loads of acidity. Critical loads, i.e. the quantity of a substance which a part of the environment can tolerate without adverse effects occurring, were determined adopting the level 0 methodology following the UN/ECE Convention on Long-range Transboundary Air Pollution. Deposition data were available for the period 1992-1997, and acidity exceedances were referred to the main vegetation types present in the area. Results showed that most part of the Estate has a medium degree of vulnerability to acidification, and the corresponding risk of acidification deriving from the exceedances of atmospheric deposition was rather low. The study of soil chemical and microbiological properties included mainly total soil organic carbon (SOC), microbial biomass-C, biomass-C/SOC, soil respiration, and metabolic quotient (qCO2). Soil organic C metabolism has been discussed on the basis of the results from eight sampling sites.
Keywords: Acidification; Atmospheric depositions; Biological indicators; Critical loads; Soil microbial biomass; Soil organic carbon

Effects of urban heavy metal pollution on organic matter decomposition in Quercus ilex L. Woods - Cotrufo, M. F.; Santo, A. V. De; Alfani, Anna (Environmental Pollution, 1995)
Decomposition of oak (Quercus ilex) leaves containing different concentrations of Fe, Zn, Cu, Cr, Ni and Pb was measured in laboratory microcosms. The leaves were collected from a polluted site inside the city of Naples and from a control site away from the city. Soil was sampled from the upper A horizon (0-5 cm) at both sites and analyzed for respiration, microbial biomass and abundance of fungal mycelia. The soils from the two sites differed significantly in heavy metals concentrations. The accumulated mass loss reached an asymptotic value after four months both for the control and polluted litters. However, control and polluted litters significantly differed in accumulated mass loss, that was respectively 40 % and 29 % of the initial weight, after 10 months. Moreover decomposition rates appeared to be strongly influenced by metal contamination in the early stages, while in later stages, they did not differ significantly. Litter respiration appeared to be inhibited by metal contamination and showed pattern and rates consistent with those found for litter decomposition. Fungal mycelia were significantly less abundant both in litter and soil from the polluted site than from the con- trol site. Metabolic activity (both as soil respiration and degree of mineralization) was lower in the polluted soil. Soil respiration and amount of soil mycelia correlated negatively with soil Pb, Zn and Cr concentration.
Keywords: Fungal biomass (voyant9; Heavy metals; litter decomposition; pollution; Soil microbial biomass; Soil respiration